FHF-independent conduction of action potentials along the leak-resistant cerebellar granule cell axon - Katarzyna Dover (Nature Portfolio, 2016)
FHFs are known to regulate voltage-gated sodium channels (NaVs). Here, the authors compare the role of FHFs in cerebellar granule cell propagation, and find NaVs in the distal axon function independently of FHFs, allowing for faster inactivation rates and reducing energy demands during repetitive spiking.